Molecular biology for green recovery-A call for action. - Marta Rodríguez-Martínez; Jens Nielsen; Sam Dupont; Jessica Vamathevan; Beverley J Glover; Lindsey C Crosswell; Brendan Rouse; Ben F Luisi; Chris Bowler; Susan M Gasser; Detlev Arendt; Tobias J Erb; et al. (PLoS Biology)
Molecular biology holds a vast potential for tackling climate change and biodiversity loss. Yet, it is largely absent from the current strategies. We call for a community-wide action to bring molecular biology to the forefront of climate change solutions.